O Banco Mundial e o documento 'Aprendizagem para todos- estratégia 2020' para a educação: uma análise da indução ao setor privado - Sampaio, Letícia Biruel [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This research aims to analyze the World Bank Document entitled “Learning for All: Strategy 2020 to education” and the induction of the private sector in the education. Interests for the study objectives, analyze the actions proposals of World Bank to privatization. The said Document, released 2011, presents a “new strategy” to educational area with actions proposals for de next 10 years. The new strategy predict three fields of action, involved: a field denominated learning (assessment of learning, assessment of impact and implementation of assessment system with tools to comparative assessment); other of technical support and financial (system of technical support, multisector approach, financing by results); and finally a field denominated strategy partners (with UN agencies, donors of committee, private sector and civil society organizations). The methodology used was documentary analysis, where the analysis focus is the induction of the private sector, considering three aspects central of the constants guidelines in the Document “Learning for All: Strategy 2020 to education” by the World Bank- education and development, sector private support and the focus on the guidelines for assessment systems. We can identify as results, before analyzing theses aspects mentioned above, we can see that the Document foundation is that education enables economic grows and fast progress, therefore as it points Santos (2004), this foundation about education reduces the individual only to his work capacity. Another present result is the strong presence of privatization in the most of the orientations in the Document, like the question about a new educational system encompassing all the formal and informal of learning, which naturalizes privatization and contributes to strengthening induction to private sector.

Esta pesquisa tem por objetivo analisar o documento do Banco Mundial intitulado “Aprendizagem para todos: estratégia 2020 para a Educação” e a indução à atuação do setor privado na educação. Interessa, para os objetivos do estudo, analisar as propostas de ação do BM para a privatização. O referido documento, divulgado em 2011, apresenta uma “nova estratégia” para a área educacional com propostas de ações para os próximos 10 anos. A nova estratégia prevê três campos de ação, envolvendo: um campo denominado de conhecimento (avaliação da aprendizagem, avaliação de impacto e implantação de sistema de avaliação com ferramentas para avaliação comparativa); outro de apoio técnico e financeiro (sistema de apoio técnico, abordagem multisetorial, financiamento por resultados) e; por fim, um campo denominado parcerias estratégicas (com agências da ONU, doadores da comunidade, setor privado e organizações da sociedade civil). A metodologia utilizada foi a análise documental, tendo como foco da análise a indução ao setor privado, considerando três aspectos centrais das orientações constantes do documento “Aprendizagem para todos: Estratégia 2020 para a educação” do Banco Mundial – educação e desenvolvimento, apoio ao setor privado e o foco nas diretrizes referentes aos sistemas de avaliação. Podemos identificar como resultados, perante a análise desses aspectos citados acima, que o fundamento do documento é que a educação possibilita crescimento econômico e progresso rápido, sendo assim como aponta Santos (2004), esse fundamento sobre a educação reduz o indivíduo apenas a sua capacidade laboral. Outro resultado presente é a forte presença da privatização na maioria das orientações contidas no documento, como a questão de um novo sistema educacional abrangendo todas as oportunidades formais e informais de ensino que naturaliza a privatização e contribui para fortalecer a indução ao setor privado.
The World Bank and the document 'Learning for all- strategy 2020 to education': an analysis of induction to the private sector
Keywords: Banco Mundial; Privatização; Avaliação